Programma: 15 juni Stray Cats; 16 juni Plastic Dolls, Eton Crop; 21 juni Cowboy Junkies; 23 juni Pere Ubu
Programma: 15 juni Stray Cats; 16 juni Plastic Dolls, Eton Crop; 21 juni Cowboy Junkies; 23 juni Pere Ubu.